The EPPO/OLAF compendium of national procedures: Bulgaria - Hauck, Pierre; Schneider, Jan-Martin; Justus Liebig University Giessen (My University, 2024)
This Bulgarian EPPO/OLAF volume starts with an introduction by Prof Dr Dobrinka Chankova providing a categorisation of the fight against EU frauds in Bulgaria. The book offers a comprehensive guide to EPPO/OLAF investigations, including case law, sources of law, and relevant institutions. In addition, the volume names relevant authorities, lists the PIF offences under Bulgarian law and provides instructions for the Court Case Access Portal. This volume is written in English and contains footnotes that reproduce the original Bulgarian legislation in Bulgarian. It also contains symbols for further information and quick reference for academics, students, practitioners and other interested readers. Prof Dr Dobrinka Chankova acted as national expert.
Keywords: ddc:340; ddc:320